Impact of COVID-19 infection in the occurrence of avascular necrosis of head of femur: a case series in a tertiary care hospital in Central Gujarat - Memon, Fatimakhatun Z.; Dumra, Gurusharan; Joshi, Dhruvi; Mehta, Vivek Vishalbhai; Shah, Nisarg (International Journal Of Community Medicine And Public Health, 2025)
Avascular necrosis (AVN) is a degenerative bone condition characterized by the death of bone tissue due to reduced blood supply. Recent studies suggest an increased incidence of AVN in post-COVID-19. This may be linked to the virus-induced hypercoagulable state and corticosteroid treatment. However, there is a dearth of evidence to substantiate this association. Therefore, this case series aims to elucidate the potential relationship between COVID-19 infection and AVN. This case series included 11 male patients (ages 25-49) diagnosed with AVN following COVID-19 infection between January 2022 and August 2023. The results indicated a higher incidence of AVN in younger males (mean age: 35 years, range: 25-49), highlighting potential age- and gender-related risks of AVN among the post-COVID-19. Despite excluding patients with pre-COVID steroid use, AVN occurred in those with steroid exposure during COVID-19 treatment and even in home-isolated cases without steroid use. Additionally, the study reported a higher side of the normal range of D-dimer and CRP levels, suggesting hypercoagulability and inflammation may have accelerated AVN progression, with concurrent alcohol and tobacco use potentially increasing risk.